Restorative Justice dalam Tinjauan Hukum Progresif: Eksistensi dan Implikasi - Wijaya, Ida Made Oka (Indonesia Berdaya, 2022)
Restorative justice is an idea in criminal law to optimize further the role of human dignity in carrying out the law. This is relevant to the idea of progressive law that is oriented towards law for humans and legal efforts to serve human dignity. The legal issue in this study is the existence of restorative justice associated with the idea of progressive law. This study aims to see the existence and implications of restorative justice associated with the idea of progressive law. This research is a normative legal research with emphasis on legal concepts that are used as the main study to analyze legal materials. This research uses a conceptual approach and a statutory approach. The legal materials in this study are primary legal materials which include: the 1945 Constitution of the Republic of Indonesia, Law no. 48 of 2009 concerning Judicial Power, as well as the Regulation of the Attorney General of the Republic of Indonesia No. 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice. The results of the study confirm that in an effort to form a progressive legal mentality, the structural aspects and legal culture need special attention and special training for law enforcement officers. In addition, the idea of restorative justice also needs to look at the concepts and practices that have developed both from abroad and in local practice in Indonesia. Abstrak: Restorative justice merupakan gagasan dalam hukum pidana untuk lebih mengoptimalkan peran martabat manusia dalam menjalankan hukum. Hal ini relevan dengan gagasan hukum progresif yang berorientasi pada hukum untuk manusia serta upaya hukum untuk mengabdi pada martabat manusia. Isu hukum dalam penelitian ini adalah eksistensi restorative justice dikaitkan dengan gagasan hukum progresif. Penelitian ini bertujuan untuk melihat eksistensi dan implikasi restorative justice dikaitkan dengan gagasan hukum progresif. Penelitian ini merupakan penelitian hukum normatif dengan menekankan pada konsep-konsep hukum yang dijadikan kajian utama untuk menganalisis bahan hukum. Penelitian ini menggunakan pendekatan konseptual dan pendekatan peraturan perundang-undangan. Bahan hukum dalam penelitian ini yaitu bahan hukum primer yang meliputi: UUD NRI 1945, UU No. 48 Tahun 2009 Tentang Kekuasaan Kehakiman, serta Peraturan Kejaksaan Republik Indonesia No. 15 Tahun 2020 tentang Penghentian Penuntutan Berdasarkan Keadilan Restoratif. Hasil penelitian menegaskan bahwa dalam upaya membentuk mental hukum progresif maka aspek struktur dan budaya hukum perlu mendapatkan perhatian tersendiri serta pelatihan khusus bagi aparat penegak hukum. Selain itu, gagasan restorative justice juga perlu melihat konsep serta praktik yang berkembang baik dari luar negeri maupun dalam praktik lokal di Indonesia.